Extraction of naphthenic acid from highly acidic oil using phenolate based ionic liquids - Nasir Shah, S. (Elsevier, 2016)
In this study, N-alkyl imidazolium ionic liquids with highly alkaline phenolate anions were used for the removal of naphthenic acid from model acid oil. The effect of alkyl spacer length on the deacidification process was evaluated by attaching butyl, hexyl, octyl, decyl and dodecyl groups on imidazolium cation. It was found that increase in the alkyl chain length increases the percent naphthenic acid removal. Extremely low amount of ionic liquids were necessary for the complete deacidification of model oil with high TAN. The reusability of the phenolate ionic liquids was also investigated. COSMO-RS calculations were performed on phenolate ionic liquids to study their extraction efficiency, selectivity and solvent capacity. Â© 2015 Elsevier B.V.